Anatomy of the olfactory bulb in Greenland shark Somniosus microcephalus (Bloch & Schneider, 1801) - FERRANDO, SARA; GALLUS, LORENZO; GHIGLIOTTI, LAURA; VACCHI, MARINO; AMAROLI, ANDREA; Nielsen, J.; Christiansen, J. S.; PISANO, EVA (Journal of Applied Ichthyology, 2017)
Gross morphology and histology of the olfactory rose e of Greenland shark Somniosus microcephalus (Bloch & Schneider, 1801), suggest a well- developed olfactory capabil- ity for this top predator and scavenger na ve to Arc c waters. In the present paper, observa ons on the olfactory rose e are reported together with the gross morphol- ogy and histology of the olfactory bulb whereby the histological analyses revealed some peculiar traits. The olfactory bulb is macroscopically divided into two sub- bulbs and a central undivided part that contain the layers typical of olfactory bulb histology. The two visible sub- bulbs are actually bundles of la olfactoria. In addi on, the olfac- tory lateral ventricle is peculiarly branched, which may increase the ependymal surface or, alterna vely, decrease the distance between the ssues of the olfactory bulb and the ventricle itself. The ependymal surface is known to be a prolifera ve zone in the olfactory bulb of shes. In Greenland shark, the olfactory epithelium showed frequent mitosis and apoptosis highligh ng the importance of this site in cell renewal. This issue should be pursued further to gain a deeper understanding of the sensory biology of Greenland shark and of elasmobranchs in general.